Bullish/bearish/neutral strategies under short sale restrictions - Bae, Kwangil; Kang, Jangkoo; Lee, Soonhee (Journal of Banking & Finance, 2016)
This study investigates the effects of short sale restrictions by extending the model of Dridi and Germain (2004) and infers informed traders’ strategies and the relation between order imbalance and price thereunder. The results are generally in line with the empirical evidence documented in the literature and are summarized as follows: First, seller-initiated trading incurs a greater price reaction. Second, short sale restrictions shift the skewness of asset returns. Third, the restrictions can stimulate investors to acquire information or increase each individual trader's order flow under the bullish and neutral signals as well as the bearish signal, which is yet to be explored empirically.